A modified fractal‐shaped slotted patch antenna with defected ground using metasurface for dual band applications. Issue 12 (20th August 2019) - Samantaray, Diptiranjan; Bhattacharyya, Somak; Srinivas, Kothapalli V.
Abstract: A novel modified fractal‐shaped slotted patch antenna employing metasurface at bottom plane along with partial ground has been proposed in this work for dual band applications with significant gain. A 4 × 5 order metasurface has been formed in the ground plane by introducing a periodic combination of two L‐type patches with centered C‐type shaped patch. The top conductor and the ground plane are designed on a 1.6 mm thick FR4 dielectric with the dimension of 28 × 28 mm 2 . The antenna is designed in such a way that it operates over the dual frequency ranges viz., 1.80 to 5.70 GHz and 10.38 to 10.94 GHz. The maximum return loss of 21 dB has been achieved over 2.60 GHz while the maximum realized gain of 7.16 dBi has been obtained at 10.92 GHz. The designed antenna offers omnidirectional radiation characteristics in the first band while directional radiation characteristics have been observed in the second band. The proposed antenna can be utilized for WiMAX 3.5/5.5 GHz, mobile, radio astronomy, and microimaging in medical analysis.